¡Vamos al Centro Comercial! Consumo y visualidades del miedo en la Medellín contemporánea (2015)
This article explores how the combination of two factors: fear andconsumer’s society have become one of the key growth driversof shopping mall in Colombia and especially in Medellin. In theseplaces, the consumption of products and services is encouragedand at the same time, consumers are invited to escape from theinherent dangers of living in a contemporary city.